Emergency medical care practitioners in the North West Province : Assessment of their understanding of the emergency services delivery environment - Redlinghys, Burl Cy Samuel (Bloemfontein: Central University of Technology, Free State, 2015)
The purpose of this study is to assess the Emergency Medical Care Practitioners’ understanding of the Emergency Medical Services delivery environment of the North West Province in which they function. The knowledge gained in this regard will then enable the North West Provincial Government to amend its policies and procedures to create a better Emergency Medical Services delivery environment in order to save lives during the so-called “golden hour”. The study was conducted amongst the different sectors of the Emergency Medical Services in the North West Province. Data was collected by means of a survey of Emergency Medical Care Practitioners with the aid of questionnaires. The data was analysed using interpretive methods of analysis in order to achieve the research objectives. Most of the responses by the Emergency Medical Care Practitioners indicate inward focussing; there is no consideration of the needs of the community. The lack of computerization in the system hampers planning processes within the service and has a negative impact on the delivery of Emergency Medical Services. The results have also shown that there is an urgent need to improve the skills levels of Emergency Medical Care Practitioners, thereby improving patient care. Emergency Medical Care Practitioners do not have a good understanding of the service delivery environment in which they operate. A multi-faceted approach is required to improve their understanding and thereby improve service delivery in the field of Emergency Medical Services in the North West Province.
Thesis
Keywords: Emergency medical services - South Africa - North West Province; Disaster relief; Emergency communication systems